Rehabilitation aimed at improving outdoor mobility for people after stroke: a multicentre randomised controlled study (the Getting out of the House Study) - Logan, Pip; Armstrong, Sarah; Avery, Tony J.; Barer, David; Barton, Garry R.; Darby, Janet; Gladman, John R.F.; Horne, Jane; Leach, Simon; Lincoln, Nadina; Mehta, Samir; Newell, Ossie; et al. (NIHR Journals Library, 2014)
Background: One-third of stroke patients are dependent on others to get outside their homes. This can cause people to become housebound, leading to increased immobility, poor health, isolation and misery. There is some evidence that outdoor mobility rehabilitation can reduce these limitations.